Characteristics and Outcome of Headache in COVID-19 Patients in a Tertiary Care Centre of Bangladesh (Journal of Dhaka Medical College, 2025)
Background: Although the symptoms of coronavirus disease 2019 (COVID-19) are predominantly respiratory. Headache is one of the most frequent neurological symptoms. There is a wide variation in the prevalence of headaches, and little is known regarding the characteristics and outcomes of headaches in COVID-19 patients. So, this study aimed to determine the characteristics and headache outcomes among COVID-19 patients.Methods: This was a hospital-based prospective cohort study conducted in Dhaka Medical College Hospital from January 2021 to December 2021. Confirmed COVID-19 patients with Reverse Transcription Polymerase Chain Reaction (RT-PCR) were enrolled in the study. The severity of the headache was assessed by the Numerical Rating Scale (NRS, 0-10). All the patients with headaches were followed up by telephonic interviews in the 2nd week and at the end of the 4th week of the onset of the headache. For patients who experienced persistent headaches after 4th week, the impact of headaches on quality of life was assessed with the Headache Disability Index (HDI).Results: We included 362 patients in this study. The majority (52.5%) of the study population belonged to severe COVID-19 infection. Fever was the most common (63.81%) symptom among the study subjects. Headache was present in 19.06% of the patients. The mean (±SD) age of participants was 54(±14.7). Patients having headaches were younger 44.2±13.8 vs 56±13.8,p